Penerapan Model Pembelajaran PBL Berbantuan Software Geogebra Untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa - Nur Icha Putri; Mukhtar Mukhtar (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
This research applies the PBL learning model with the help of Geogebra software to test the increase in junior high school students' ability to understand mathematical concepts. This research aims to find out whether the application of the PBL learning model assisted by Geogebra software can improve students' ability to understand mathematical concepts. The research method used is Classroom Action Research. The subjects of this research were 29 students in class VII-6 of SMP Negeri 17 Medan. The object of this research is to increase students' understanding of mathematical concepts in set material with the PBL model assisted by Geogebra software. Based on the research results obtained, in cycle I the number of students who completed classical learning was 8 students (27.59%), and 21 students (72.41%) had not yet completed it, with an average class score of 54.87. In cycle II there was an increase in students' ability to understand mathematical concepts, there were 21 students (72.41%) who achieved completeness and 8 students (27.59%) who had not yet completed it, with a class average score of 72.24. The target percentage level of student success based on the second cycle test of understanding mathematical concepts has reached the specified completeness, namely 70% with a KKM of 70. Based on the research results, it can be concluded that the application of the Problem Based Learning (PBL) model assisted by Geogebra software can improve the ability to understand mathematical concepts student.